1990
DOI: 10.1002/mds.870050403
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol‐responsive myoclonic dystonia in a large family: Dominant inheritance and phenotypic variation

Abstract: Alcohol-responsive myoclonic dystonia is reported in 26 individuals in a six-generation family, thus indicating autosomal dominant inheritance. Twenty affected family members aged between 3 and 56 years were examined on one occasion. Myoclonus in arms, shoulder, and neck distribution was seen in 17, with occasional generalized jerks in 14. Leg dystonia/hemidystonia was seen in two infant cases, writer's cramp in seven, torticollis/retrocollis in two, and finger tremor in three. The onset of myoclonus was regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
36
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(41 citation statements)
references
References 14 publications
(7 reference statements)
4
36
0
Order By: Relevance
“…In these families, myoclonus may occur alone or associated with dystonia or sometimes tremor. Isolated dystonia (as initial hemidystonia) was reported in two infants, shortly preceding the appearance of myoclonus, but had largely disappeared by the age of 3 years (26). Of 15 family members reported by Korten et al (27), eight had myoclonus alone; four, myoclonus and tremor; and three, tremor alone.…”
mentioning
confidence: 95%
“…In these families, myoclonus may occur alone or associated with dystonia or sometimes tremor. Isolated dystonia (as initial hemidystonia) was reported in two infants, shortly preceding the appearance of myoclonus, but had largely disappeared by the age of 3 years (26). Of 15 family members reported by Korten et al (27), eight had myoclonus alone; four, myoclonus and tremor; and three, tremor alone.…”
mentioning
confidence: 95%
“…Kramer, unpubl.). Genes responsible for other hereditary types of dystonia, including rapid-onset (Dobyns et al 1993), myoclonic (Kurlan et al 1988;Kyllerman et al 1990), and other late-onset focal dystonias (Forsgren et al 1988;Bressman et al 1994a) have not been mapped yet.…”
mentioning
confidence: 99%
“…A 3-bp deletion in the DYT1 gene causes the majority of cases of early-onset primary torsion dystonia (7), and linkage to the DYT1 locus has been excluded in several families with MD (8,9), including the one under study (data not shown). Despite the description of various large families with MD in the literature (3,(8)(9)(10)(11)(12)(13), as yet, no positive linkage has been reported to a chromosomal location.…”
mentioning
confidence: 99%
“…In addition, the DRD2 receptor is believed to have a role in affect, emotion, and reward mechanisms (14) and has been implicated in the etiology of alcoholism (20,21) and schizophrenia (22). Interestingly, many patients with MD consume large quantities of alcohol (8), frequently exceeding the amount necessary to relieve the myoclonus, or even to be addicted to alcohol or drugs (11). Some patients, including several members of the family under study, also display features of psychiatric disorders͞affective traits such as anxiety, neurosis, phobias (11), depression, and panic attacks (M.F.B.…”
mentioning
confidence: 99%